Teaching self-management training conditions for the activities part-time students (Pedagogy of Higher and Secondary Education, 2012)
Nesterenko V. Teaching self-management training conditions for the activities part-time students.The article deals with the didactic conditions which provide the management of part-time students’ independent educational activity. The approaches which form the methodological basis for the didactic conditions aimed at managing part-time students’ independent educational activity are described.
Keywords: didactic conditions; educational activity; part-time students; approaches; management of part-time students’ independent educational activity